Fungsi Hizb Sulaiman dan Isim Petak: Kajian Filologi Atas Serat Wirid Kagem Dal(e)m Nata (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
This study is intended to describe the condition of the Serat Wirid Kagem Dalem Nata text, the meaning of the text using the hermeneutic theory to describe the function of the wirids or prayers practiced by the Islamic Mataram dynasty kings and Islamic boarding schools especially Hizb Sulaiman and Isim Petak along with their prayers other prayers, which are contained in the manuscript Serat Wirid Kagem Dalem Nata. The object of this research is the NB manuscript. 506 collections of National Library of Indonesia. The results of this research are the results of the meaning of the text. Editing Serat Wirid Kagem Dalem Nata means preparing a manuscript that is ready for publication or print. Editing in philology is providing manuscripts that are close to the original, namely good and correct manuscripts. Good means easy to read and understand because it has been transcribed or transliterated (from Javanese script to Latin script) and the spelling has been adapted to the target language. Correct means that the validity of the contents of the text can be accounted for, because it has been cleared of typographical errors. Keywords: Philology, Serat Wirid, Text Editing, Hermeneutics, Hizb, Isim.